2004
DOI: 10.1007/s00418-004-0715-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical distribution of somatotrophs in porcine anterior pituitary

Abstract: The objective of this immunohistochemical study was to identify the spatial distribution patterns of growth hormone (GH) secreting cells (somatotrophs) in the newborn and prepubertal porcine pituitary. No differences were observed among the total somatotrophs per unit area across the three ages. There were, however, changes in spatial distribution of somatotrophs in porcine pituitary with developmental age. Distinctive characteristics of the pattern included a high population of somatotrophs (44 +/- 1.2; mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Similar results were reported by other authors who have demonstrated that testosterone has an effect on the GH cells [Wehrenberg et al, 1985;Hertz et al, 1989;Kineman et al, 1990]. Investigations carried out in mink [Vidal et al, 1994], B. arenarum [Miranda et al, 1996], Anguilla anguilla L. [Grandi et al, 2003] and pig [Lee et al, 2004] of different ages showed morphometric differences of the somatotrophs probably due to the different physiological stages. In viscacha, the castration provoked a significant decrease in the immunopositive area, in the number of cells and in the major cellular diameter, and when studying the different growth stages, a gradual increase in these parameters was observed in relation to the degree of the testicular activity.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Similar results were reported by other authors who have demonstrated that testosterone has an effect on the GH cells [Wehrenberg et al, 1985;Hertz et al, 1989;Kineman et al, 1990]. Investigations carried out in mink [Vidal et al, 1994], B. arenarum [Miranda et al, 1996], Anguilla anguilla L. [Grandi et al, 2003] and pig [Lee et al, 2004] of different ages showed morphometric differences of the somatotrophs probably due to the different physiological stages. In viscacha, the castration provoked a significant decrease in the immunopositive area, in the number of cells and in the major cellular diameter, and when studying the different growth stages, a gradual increase in these parameters was observed in relation to the degree of the testicular activity.…”
Section: Discussionsupporting
confidence: 78%
“…Besides, the immunolabeling in the intercellular space suggests that a greater secretion of GH might exist in the reproductive and gonadal recovery periods than in the gonadal regression period of the reproductive cycle. Lee et al [2004] reported changes in the spatial distribution through age in porcine suggesting that there may be regional specificity in the cellular differentiation and transformation during growth. In viscachas, we have also observed a small sector delimited by long blood vessels where there were no immunopositive cells, as opposed to what has been observed in immature animals in which this distribution was not so evident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an immunohistochemical study, the spatial distribution patterns of growth hormone (GH) secreting cells (somatotrophs) in the newborn and prepubertal porcine pituitary were analyzed (Lee et al 2004). Although no developmental differences were observed among the total somatotrophs per unit area, regional differences of varying degree in their spatial distribution were noted during development.…”
Section: Hormones: Cellular Origin and Cellular Effectsmentioning
confidence: 99%
“…Age-associated changes in the spatial distribution patterns of growth hormone (GH)-containing cells in the newborn and prepubertal porcine anterior pituitary were documented in a detailed study by Lee et al (2004). The finding that the number of immunopositive somatotrophs per unit area in the entire pituitary did not significantly differ between 1-, 42-, and 100-day-old animals was interpreted as showing that changes in circulating GH concentrations in the young pig were caused by an increase not in size but in total number of somatotrophs, as the weight and size of the pituitary increased.…”
Section: Endocrine Systemmentioning
confidence: 99%